Pengaruh Modifikasi Pembelajaran Menggunakan Media Kardus Terhadap Hasil Belajar Lompat Jauh Gaya Jongkok Pada Siswa Kelas VI SD Negeri Sidomukti III Bojonegoro - Dwi Retno Aryaningtyas; Muhammad Muhyi Faruq; Yandika Fefrian Rosmi (Corner: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
This study was to determine the effect of learning modification using cardboard media on learning outcomes squat-style long jump in grade VI SD Negeri Sidomukti III Bojonegoro. This research is an experimental study that focuses on "Two Groups Pretest Posttest Design", namely a research design that contains a pre-test before being given treatment and a post-test after being given treatment. This study used statistical data analysis methods with the formula used was the T test. Based on this research, it can be stated that from the two groups there have been differences in the improvement of learning outcomes squat-style long jump skills through modification of learning using cardboard media. When comparing the total number of differences from each of these groups, the average number of differences in the exercise group using modification (experimental group) is 1.850 on average, and the average posttest is 2.70 and the t-count value in the experimental group 5.075 and a probability value of 0.000 ,, which means there is a difference before and after the provision of learning modification training using cardboard media to the squat style long jump skill in the experimental group